PENGARUH HARGA DAN LOKASI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA WISATA KK26 SITUBONDO - S, Yayuk; Karnadi, Karnadi; Harisandi, Yudhistira (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is an interconnected activity between companies and consumers as a system to generate profits, for that the right marketing strategy can increase tourist attractiveness through Price, Location, Consumer Satisfaction and Loyalty of KK26 tourism consumers in Situbondo Regency. The purpose of this study was to analyze and test the effect of price and location in determining consumer loyalty with consumer satisfaction as an intervening variable. The population in this study are KK26 tourism consumers in Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that price has a significant positive effect on consumer satisfaction, location has a significant positive effect on consumer satisfaction, price has a positive but not significant effect on consumer loyalty, location has a positive but not significant effect on consumer loyalty, satisfaction consumers have a significant positive effect on consumer loyalty. The results of the indirect influence hypothesis show that the price variable on consumer loyalty through consumer satisfaction has a significant positive effect, location on consumer loyalty through consumer satisfaction has a significant positive effect.